New Frontiers in the Treatment of Overactive Bladder and Incontinence - Chancellor, Michael B (MedReviews, LLC, 2002)
In this article the author tries to forecast how urologists will treat the overactive bladder (OAB) in the next decade. He reviews drugs currently under development and also logical and exciting pharmacological targets that would be suitable targets for treating OAB in the future. The author also discusses intravesical therapy and alternative drug delivery methods, such as intravesical capsaicin and botulinum toxin. There are many advantages to advanced drug delivery systems, including the achievement of long-term therapeutic efficacy, decreased incidence and severity of side effects, and improved patient compliance. Special emphasis is placed on approaches to modulating bladder afferent nerve function to prevent OAB. Speculation on future techniques such as gene therapy can also be considered for treating OAB, because they may make it possible to access all of the genitourinary organs via minimally invasive techniques. Traditional anticholinergic therapies are limited in their effectiveness. There is great hope for future research and therapy for OAB and urinary incontinence.